Empirical modeling of deprivation contagion among social exclusion dimensions (using MCMC methods) - Ambra Poggi; Xavier Ramos (Institute for the Study of Labor (IZA), 2007)
Economic theory and empirical evidence clearly show that social exclusion dimensions are inter-related. Notwithstanding that, dimensions are usually assumed independent from one another in the economics literature. In this paper we explore the inter-dependency of social exclusion dimensions and study the transmission of deprivation among them. In particular, we propose the use of stochastic epidemic models, which are typically used to study the transmission of infectious diseases, to the analysis of deprivation diffusion among social exclusion dimensions with the aim of acquiring a deeper understanding of the mechanism governing deprivation transmission. We also provide an empirical implementation that investigates the consequences, in terms of future deprivation, for Italian and Spanish women of being jobless, as opposed to doing paid work. We also investigate the consequences of being unemployed versus being inactive. We conclude that working seems to act as a protective mechanism to shocks. In addition, conditional on losing one's job, women who subsequently search for a job (unemployed) are more likely to experience contagion than women who do not search (inactive)
urn:nbn:de:101:1-2008042275
Keywords: 330; Soziale Isolation; Ansteckungseffekt; Frauenarbeitslosigkeit; Frauenerwerbstätigkeit; Markovscher Prozess; Schätzung; Italien; Spanien